The Impact of Gender Equality on Female Employees’ Career Development in a Chinese Internet Company - Fu, Wenyi (2022)
Gender equality at work is a long-term objective shared by contemporary organisations. In Internet and technology industry, there has been quite a disparity in opportunities and treatment for male and female employees in their career development, but the influencing factors for such gender gaps still remain to be explored. This research aims to explore the influencing factors of gender equality in the career development of female employees in the Chinese IT organisation A through qualitative research. Specifically, the method of semi-structured interviews was adopted in this study to reveal the gender inequality related factors that hinder the career paths of female employees in the IT organisation A and figure out the relationships between them. As indicated by the research findings, glass ceiling and gender stereotypes are considered as the impacting factors that cause gender inequality in the IT organisation A, imposing obstacles to the career development of female employees in the company. After perceiving and experiencing gender inequality or discrimination in the workplace, the engagement level of female employees in the IT organisation A has witnessed a decline to a certain extent. In addition, this research also put forward feasible suggestions for promoting gender diversity and inclusion in organisations from four dimensions of human resource management.